(untitled) (UUM Journal of Legal Studies, 2017)
Abstract: Bank customers/consumers are the drivers of the banking industry. Their protection should be a priority. This is because consumer protection boosts consumer confidence and enhances banking quality. This may be the reason the Central Bank of Nigeria (CBN) made consumer protection part of its reform policies in the banking industry. This paper examined the legal regime on banking regulation and consumer protection. The banking sector regulatory laws were critically examined. These included the Consumer Protection Council Act, 1992, the Banking Act 1969, and the Central Bank of Nigeria Act 2007, etc. The analysis revealed that the banking laws and the regulatory institutions provide inadequate protection for the banking consumer. This is a cause for concern to the banking consumers in the country. This state of things could be considered as the contributory fact or for growing consumer rights abuses and humiliation in the Nigerian banking industry. Keywords: Consumer abuses, Legal regime, Central Bank, Regulatory, Nigeria. Abstrak: Pelanggan bank/pengguna merupakan penggerak kepada industri perbankan. Perlindungan kepada mereka sepatutnya menjadi keutamaan. Ini adalah kerana perlindungan kepada pengguna akan menggalakkan keyakinan pengguna dan meningkatkan lagi kualiti perbankan. Perkara ini mungkin menjadi alasan Bank Negara Nigeria menjadikan perlindungan pengguna sebahagian daripada polisi pembaharuannya dalam industri perbankan. Artikel ini mengupas rejim perundangan berkaitan peraturan perbankan dan perlindungan pengguna. Undang-undang perintah sektor perbankan dikaji secara kritikal. Undang-undang ini termasuklah Consumer Protection Council Act 1992, Banking Act 1969, Central Bank of Nigeria Act 2007 dan lain-lain. Analisis telah menunjukkan bahawa undang-undang perbankan dan institusi-institusi berkaitan menyediakan perlindungan yang tidak mencukupi kepada pelanggan bank. Ini merupakan sebab utama kepada keprihatinan terhadap pengguna-pengguna perbankan di negara ini. Keadaan ini boleh dianggap sebagai fakta penyumbang kepada peningkatan penyalahgunaan hak-hak pengguna dan penindasan dalam industri perbankan di Nigeria. Kata kunci: Penindasan pengguna, Rejim undang-undang, Central Bank, Peraturan, Nigeria.